2014
DOI: 10.2320/matertrans.m2013227
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Grain Boundary Migration during Recrystallization within the Bulk of a Moderately Deformed Aluminium Single Crystal

Abstract: A single grain growing in the bulk of a mildly deformed (30% thickness reduction through cold rolling) aluminium single crystal with an f001gh100i orientation (Cube orientation), is monitored during recrystallization with synchrotron radiation using topo-tomography. The formation and migration of planar boundary segments (facets) are analyzed using a method that determines the displacements of local boundary segments along parallel lines perpendicular to the facet plane. Facets are observed to form after a cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…During the past few years, in-situ 3-dimensional X-ray diffraction (3DXRD) experiments have been used to observe the growth of recrystallizing grains in the bulk of deformed metals [1,2]. It has been revealed that the nuclei do not grow in a homogeneous manner with constant moving speed as described in classic models, but occur with variations at the local scale: most boundary segment move in a jerky stop-go mode, with locally large protrusions and retrusions forming and disappearing as the boundary migrates [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past few years, in-situ 3-dimensional X-ray diffraction (3DXRD) experiments have been used to observe the growth of recrystallizing grains in the bulk of deformed metals [1,2]. It has been revealed that the nuclei do not grow in a homogeneous manner with constant moving speed as described in classic models, but occur with variations at the local scale: most boundary segment move in a jerky stop-go mode, with locally large protrusions and retrusions forming and disappearing as the boundary migrates [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that the nuclei do not grow in a homogeneous manner with constant moving speed as described in classic models, but occur with variations at the local scale: most boundary segment move in a jerky stop-go mode, with locally large protrusions and retrusions forming and disappearing as the boundary migrates [1,2]. Exsitu electron backscattered diffraction (EBSD) and electron channeling contrast (ECC) studies of local boundary migration have also revealed similar migration behavior [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown by molecular dynamic (MD) simulations that boundaries with rough morphologies have high mobility while smooth boundaries can lead to stagnation of boundary motion [3]. Direct experimental observations of recrystallization boundary migration in 4 dimensions (4D -x, y, z and time) using synchrotron X-ray techniques have revealed that recrystallizing boundaries migrate in a non-homogeneous manner both temporally and spatially: the boundaries migrate in a 'stop-go' manner and the boundaries may be rough with protrusions and retrusions [4,5]. These rough features have also been observed using 2-dimensional characterization techniques such as electron channeling contrast (ECC) or electron backscattered diffraction (EBSD) [e.g.…”
mentioning
confidence: 98%
“…[55] To overcome this limited spatial resolution, the topo-tomography technique, which is a kind of 3DXRD, has recently been used to follow the growth of a recrystallized grain in a deformed single crystal of near cube orientation [55]. Figure 11 shows the grain after different annealing times [55]. As this technique gives a better spatial resolution of 1.4 µm along all directions, details of the local protrusions/retrusions and facets on the boundary are clearly visualized, and quantifications of boundary morphology are possible.…”
Section: Watching Growth Of Individual Grains Into a Lightly Deformedmentioning
confidence: 99%
“…The displacements of local grain boundary segments are characterized by the distances of the successive intersection points along the parallel lines to their reference positions (which are the positions of the intersection points at 1719 s). [55] To overcome this limited spatial resolution, the topo-tomography technique, which is a kind of 3DXRD, has recently been used to follow the growth of a recrystallized grain in a deformed single crystal of near cube orientation [55]. Figure 11 shows the grain after different annealing times [55].…”
Section: Watching Growth Of Individual Grains Into a Lightly Deformedmentioning
confidence: 99%